Conversion of Aromatic Amino into Trifluoromethyl Groups through a Sandmeyer-Type Transformation - Wang, Xi; Xu, Yan; Zhou, Yujing; Zhang, Yan; Wang, Jianbo (Synthesis, 2014)
A novel strategy for aromatic trifluoromethylation by converting amino into trifluoromethyl groups via a Sandmeyer-type reaction is reported. The transformation involves diazotization of the aromatic amines with tert-butyl nitrite and hydrochloric acid to form aryldiazonium chlorides, followed by trifluoromethylation with trifluoromethylsilver at low temperature. Various readily available aromatic amines are smoothly converted under mild conditions.
Keywords: trifluoromethylation; aromatic amines; diazonium salts; silver; Sandmeyer reaction